2007 IEEE 23rd International Conference on Data Engineering 2007
DOI: 10.1109/icde.2007.367905
|View full text |Cite
|
Sign up to set email alerts
|

Representing and Querying Correlated Tuples in Probabilistic Databases

Abstract: Probabilistic databases have received considerable attention recently due to the need for storing uncertain data produced by many real world applications. The widespread use of probabilistic databases is hampered by two limitations: (1) current probabilistic databases make simplistic assumptions about the data (e.g., complete independence among tuples) that make it difficult to use them in applications that naturally produce correlated data, and (2) most probabilistic databases can only answer a restricted sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
187
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 33 publications
0
187
0
Order By: Relevance
“…A similar concept is used in many tuple uncertainty models to track correlations between tuples. [9] uses lineage and [14] uses factor tables to capture such dependencies. As we are interested in capturing historical dependencies between attributes of tuples, our concept of dependencies is different from this related work, which capture these dependencies on a per tuple basis.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar concept is used in many tuple uncertainty models to track correlations between tuples. [9] uses lineage and [14] uses factor tables to capture such dependencies. As we are interested in capturing historical dependencies between attributes of tuples, our concept of dependencies is different from this related work, which capture these dependencies on a per tuple basis.…”
Section: Historymentioning
confidence: 99%
“…The ProbView system [16] took a similar approach by propagating the formulas necessary to evaluating the resulting probabilities. Sen et al have more recently proposed an alternative approach to represent tuple correlations using probabilistic graphical models [14]. They use factored representations of the relations to represent their dependencies.…”
Section: Overhead Of Historiesmentioning
confidence: 99%
“…However, because of the independence assumption, it is non-trivial to extend our exact algorithm to tackle the problem against dataset with correlations. As a possible future work, we will consider to develop efficient exact algorithm based on the graph model [38,15] which can effectively capture the correlations of the uncertain dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty is inherent in such applications due to various factors such as data randomness and incompleteness, limitation of equipment, and delay or loss in data transfer. A number of issues have been recently addressed; these include modeling uncertainty [2,36], query evaluation [10,13,14,37], indexing [11,41], top-k queries [22,35,39,42], skyline queries [34], joins [26,27], nearest neighbor query [5,9,27], clustering [28,30], etc.…”
Section: Introductionmentioning
confidence: 99%
“…General issues in modelling and managing uncertain data are addressed by Dey and Sarkar in [4], Lee in [11], and Antova, Koch, and Olteanu in [6]. Querying uncertain data by the probabilistic paradigm has been investigated by Dalvi and Suciu in [2] and Sen and Deshpande in [17]. Very recently Dalvi and Suciu [3] have shown that the problem of query evaluation over probabilistic databases is either P T IM E or #P -complete.…”
Section: Related Workmentioning
confidence: 99%